Analisis Kesalahan Siswa Kelas Viii Dalam Menyelesaikan Soal Ujian Akhir Semester Genap Di Smp N 1 Kebakkramat Tahun Ajaran 2014 - 2015 - Pertiwi, Dian (2016)
This study aims to identify and describe the types of errors and factors that cause students to make mistakes in doing the exam end of semester. This research is a qualitative descriptive study. Subjects were students of class VIII D, E, F SMP N 1 Kebakkramat. The main data sources in the form of words and actions rest is additional data such as documents, data and actions of students who were interviewed and pengampu mathematics. Data collected by observation, interview and documentation. Data validation was done by triangulation, namely techniques and sources. Data were analyzed using qualitative data analysis, namely data reduction, data presentation, and conclusion. The results showed that the fault location dilakuakan students are misconceptions, language interpretation, and calculation procedures. Misconceptions that the students include students in writing a formula error, the error did not write formulas and errors in interpreting the operation. Misinterpretation of the language that the students include students can not create a mathematical model that is associated with everyday language. Errors procedures performed include the students in taking steps to resolve the error and the error did not finish his work. In addition miscalculation of the student is a mistake in the case of addition, subtraction, multiplication and division. While the causes are less conscientious student, do not understand the purpose of a matter, not knowing the concept of the formula and the misconceptions between teacher and pupil.